Hyperprolactinemia in Subclinical Hypothyroid Patients at BPKIHS, Dharan - Tamrakar, Rajendra; Rai, Avinas; Maskey, Robin (Journal of Nobel Medical College, 2023)
Background: Hyperprolactinemia and subclinical hypothyroidism may be associated and are usually accompanied by menstrual disorders in female patients. The objective of this study is to determine the prevalence and association of hyperprolactinemia in subclinical hypothyroidism and the associated clinical features. Materials and Methods: This is a hospital-based descriptive cross-sectional study conducted from 1 July 2022 to 31 December 2022. Serum Prolactin level was measured in subclinical hypothyroid patients who met the inclusion criteria.Descriptive statistics such as frequency and percentage for categorical variables and mean with standard deviation for quantitative variables were calculated. Pearson’s Chi-square test was used for statistical analysis and the p-value <0.05 was considered statistically significant for analysis. Results: One hundred and forty-four newly diagnosed subclinical hypothyroid patients were enrolled; the mean age of the patients was 36.95±12.58 years. Female patients comprised 89.6% of the study participants. Hyperprolactinemia was prevalent in 23.6% of subclinical hypothyroid patients (23.4% in TSH 4.5-10 µIU/mL group and 24.3% in TSH >10 µIU/mL group). There was no significant association between subclinical hypothyroidism and prolactin levels.Menstrual irregularities were the most common clinical manifestations which account for 44.2% of female subclinical hypothyroid patients and menstrual irregularities were significantly associated with hyperprolactinemia. Conclusion: The number of patients with hyperprolactinemia in subclinical hypothyroidism was substantial even though the association between them was not significant. Assessment of serum prolactin may be considered in subclinical hypothyroid patients who present with menstrual irregularities